2020
DOI: 10.1093/molehr/gaaa063
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic fatty acid metabolism in diabetic pregnancy: the difference between embryoblasts and trophoblasts

Abstract: During the first days of development the preimplantation embryo is supplied with nutrients from the surrounding milieu. Maternal diabetes mellitus affects the uterine microenvironment, leading to a metabolic adaptation processes in the embryo. We analysed embryonic fatty acid (FA) profiles and expression of processing genes in rabbit blastocysts, separately in embryoblasts and trophoblasts, to determine the potential consequences of maternal diabetes mellitus on intracellular FA metabolism. Insulin-dependent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Palmitic acid is a straight chain saturated fatty acid that can be absorbed from food or generated from the endogenous synthesis of some other fatty acids, carbohydrates and amino acids ( Innis, 2016 ). It was reported that palmitic acid may have adverse impacts on conception and preimplantation embryo development ( Innis, 2016 ; Rampersaud et al, 2020 ; Schindler et al, 2020 ). Interestingly, fetuses were found to accumulate palmitic acid during the last trimester of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid is a straight chain saturated fatty acid that can be absorbed from food or generated from the endogenous synthesis of some other fatty acids, carbohydrates and amino acids ( Innis, 2016 ). It was reported that palmitic acid may have adverse impacts on conception and preimplantation embryo development ( Innis, 2016 ; Rampersaud et al, 2020 ; Schindler et al, 2020 ). Interestingly, fetuses were found to accumulate palmitic acid during the last trimester of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the metabolic profiles of the EB and TB cells are differentially affected by maternal diabetes mellitus [36]. While saturated fatty acids (palmitic and stearic acid) were elevated in the EB cells of diabetic rabbits, polyunsaturated fatty acids, such as docosahexaenoic acid, were decreased [36]. In contrast, lower levels of palmitic and stearic acid and higher levels of oleic acid were observed in the TB cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, EB cells tend to accumulate intracellular lipid droplets and predominantly express FABP4 and adipophilin genes [35]. In addition, the metabolic profiles of the EB and TB cells are differentially affected by maternal diabetes mellitus [36]. While saturated fatty acids (palmitic and stearic acid) were elevated in the EB cells of diabetic rabbits, polyunsaturated fatty acids, such as docosahexaenoic acid, were decreased [36].…”
Section: Introductionmentioning
confidence: 99%